The Influence of Growth Opportunities, Debt Covenant, Capital Intensity, and Financial Distress on Accounting Conservatism - Dian Kusumawati; Devi Febrianti; Amrizal Imawan; Ninik Mas'adah (Cita konsultindo, 2026)
The purpose of this research is to dissect the relationship between accounting conservatism and growth prospects, debt covenants, capital intensity, and financial hardship. Medical providers trading on the Indonesia Stock Exchange between 2020 and 2023 were the focus of this study. Using secondary data collected from healthcare industry annual reports and audited reports, this quantitative research examined the topic. A total of 108 data points were collected using the purposive sampling method. A multiple linear regression analysis was performed on this research. We used IBM SPSS version 25 to do the analysis. The findings revealed that accounting conservatism was impacted by capital intensity, while growth prospects, debt covenants, and financial difficulties were not. This discovery lends credibility to the idea that capital intensity could back conservative practices in corporate accounting. In the healthcare industry, the primary variables that led to the adoption of conservative accounting practices over the research period were not development prospects, as assessed by sales growth and debt covenants, as proxied by DAR, and financial hardship, as evaluated by the Altman Z score. The findings of this study have practical relevance for managers' decision-making processes and provide empirical support to the growing body of literature on sustainable practices and conservative accounting.